The role of relationship capital in Malaysian public sector collaboration outcomes - Ramadass, Shila Devi; Sambasivan, Murali; Xavier, John Antony (2013)
The topic of public sector collaboration (PSC) is at the forefront for prominent scholars in recent years as a vehicle in solving atrocious social problems. Despite the value of PSC to the improvements in the real world, PSC processes have remained conceptually obscure which is known as the 'black box'. In this paper, the authors brings together theoretical and empirical literature, references to secondary data combined with a Malaysian case study of public agencies involved in PSC to better understand the role of relationship capital in shaping successful PSC outcomes. The paper reveals that relationship capital is a crucial factor in PSC process for fulfilling national priority areas by solving complex social problems in Malaysia. It is also found that relationship capital contributes towards value creation as well as positive re-evaluation of collaboration partners.